Sons from afar - Voigt, Cynthia (New York : Fawcett Juniper, 1991)
Six years after coming to live with their grandmother, James and Sammy Tillerman go in search of their longlost father.
7.0
Young Adult
Young Adult
Notable/Best Books (A.L.A.)
Publisher's Weekly
Booklist
Keywords: Fathers -- Fiction; Brothers -- Fiction; Fathers -- Fiction; Brothers -- Fiction